Representing transformation through visual experimentation - Pedersen, Pia (InfoDesign, 2014)
The core concept of this visual experiment is “transformation,” an approach to the visualisation of information, which was developed in the 1920s based on ISOTYPE (an acronym for International System Of TYpographic Picture Education). In the present on-going PhD-project—where research through design and design history are intertwined—visual experimentation is central for understanding what rests within original Isotype material. Two visual experiments have already been conducted each of them presenting a different angle towards widening the theory on transformation. This paper presents the third experiment that accumulates and extends the previous two experiments by reusing and revising both their visual methodologies and gained knowledge. The purpose is to go one step deeper into the material in order to understand how it is possible to work with transformation in design. With a critical look at the earlier experiments, the notion of transformation is now presented again through a series of visualisations. As a consequence the paper offers two angles towards information design, first how information design methods can be employed as a toll for research, second how the research reveals new details and principles in the process of transformation and adds to the field of information design.